Reduction of flux-creep in magnetized bulk HTS by use of permanent magnets. (15th November 2016) - Parks, D; Weinstein, R; Davey, K; Sawh, R-P; Carpenter, K
Abstract: We report the effect of permanent magnet (PM) collars on the flux-creep rate of magnetized bulk HTS. The creep rates of single-grain, cylindrical samples are measured with attached collars activated to various fields, B PM, in the range 0 ≤  B PM  ≤  B PM, max, where B PM, max is the fully saturated field of the PM. As B PM varies, the creep rate of the HTS is found to maintain its well-known form—a constant fractional loss λ, of original residual field, per decade of time. However, the magnitude of λ decreases as B PM increases. The decrease in λ is found to be linearly dependent on increasing B PM . The collar field for which flux-creep extrapolates to zero is found to be comparable to the maximum trappable field of the HTS bulk, B T, max . The properties of the dependence of λ on the HTS peak field, B T, max, the PM field, B PM, and the creep rate λ 0 with B PM  = 0 permit the reduced creep rate in these experiments to be predicted by a universal equation.